1999
DOI: 10.1074/jbc.274.19.13017
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Hamster Ovary Cell Mutants Defective in Glycosaminoglycan Assembly and Glucuronosyltransferase I

Abstract: The proteoglycans of animal cells typically contain one or more heparan sulfate or chondroitin sulfate chains. These glycosaminoglycans assemble on a tetrasaccharide primer, -GlcA␤1,3Gal␤1,3Gal␤1,4Xyl␤-O-, attached to specific serine residues in the core protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 86 publications
0
95
0
1
Order By: Relevance
“…cDNAs encoding human GalT-I (16,17) and human/mouse GalT-II (18) have been cloned based on the analysis of expressed sequence tags (EST). cDNAs for human and hamster GlcAT-I have been cloned based on the sequence homology to rat GlcAT-P that synthesizes the HNK-1 carbohydrate epitope on glycoproteins (19) and by expression cloning, respectively (20). Transcripts of the four genes are differentially yet broadly expressed in human tissues (15,17,18,21), consistent with the ubiquitous distribution of GAGs (Table 1).…”
Section: Formation Of the Glycosaminoglycan-protein Linkage Regionmentioning
confidence: 93%
“…cDNAs encoding human GalT-I (16,17) and human/mouse GalT-II (18) have been cloned based on the analysis of expressed sequence tags (EST). cDNAs for human and hamster GlcAT-I have been cloned based on the sequence homology to rat GlcAT-P that synthesizes the HNK-1 carbohydrate epitope on glycoproteins (19) and by expression cloning, respectively (20). Transcripts of the four genes are differentially yet broadly expressed in human tissues (15,17,18,21), consistent with the ubiquitous distribution of GAGs (Table 1).…”
Section: Formation Of the Glycosaminoglycan-protein Linkage Regionmentioning
confidence: 93%
“…Flow Cytometry Analyses with FGF-2-This assay was performed as described previously (19). Biotinylated fibroblast growth factor 2 (FGF-2) was graciously provided by Dr. Jeff Esko of the University of California at San Diego.…”
Section: Northern Blot Rt-pcr and Real-time Rt-pcr-poly(a)mentioning
confidence: 99%
“…Xylosyltransferase (2), galactosyltransferase I (GalTI) 1 (3,4), and glucuronosyltransferase (GlcATI) (5,6) have been cloned and partially characterized. In addition, mutant cell lines have been identified that contain defects in each of these enzymatic steps (7)(8)(9), and C. elegans mutants in GalTI (sqv3) and the GlcATI (sqv8) have been described, demonstrating the importance of these reactions and glycosaminoglycans in cellular processes and organismal development (10,11). The enzyme that transfers the second galactose unit, galactosyltransferase II (GalTII) has not yet been identified.…”
mentioning
confidence: 99%